Health : - Webb, Frances Sizer (West Educational Publishing, 1999)
Health: Making Life Choices gives students the important decision-making skills and information they need to promote their own good health. It teaches the self-responsibility and skills needed to allow students to make wise lifestyle choices--the key to living a long and happy life.